The tibial insertion of the hamstring can be considered to be preserved during anterior cruciate ligament reconstruction - Fang, Kaibin; Dai, Zhangsheng; Lin, Xiaocong (Frontiers in Surgery, 2022)
Aim: In order to investigate whether it is beneficial for patients to preserve the transpedicular insertion of hamstring when using the hamstring as a graft for anterior cruciate ligament reconstruction. Methods: This is a retrospective study.Patients with anterior cruciate ligament injury who underwent surgery in a large hospital from January 2015 to may 2021 were included in the study. These patients underwent anterior cruciate ligament reconstruction assisted by arthroscopic . Autologous hamstring muscles were used as grafts. Patients whose hamstring were preserved during the operation were included in the observation group. The remaining patients were included in the control group. The knee joint function and operation of the two groups were compared. Results: There was no statistical difference between the two groups in general data including gender, age and surgical side. All the patients' operations were successfully completed There was no significant difference in the operation time between the two groups.All patients were followed up for at least one year. No patients had complications such as wound infection and graft failure at the last follow-up. There was no significant difference between the two groups in Lysholm score and IKDC score before operation. Similarly, there was no significant difference between the two groups in Lysholm score and IKDC score three months after operation. However, the Lysholm score and IKDC score of the two groups one year after operation were statistically different, and the patients in the observation group had higher Lysholm score and IKDC score. After comparing the MRI images of the knee joints of the two groups three months after operation through the MRI evaluation system, compared with the patients in the control group, the patients in the observation group have higher scores, and the difference is statistically significant. Conclusion: In the knee arthroscopic assisted anterior cruciate ligament reconstruction using the popliteal muscle as a graft, the tibial insertion of the popliteal muscle can be preserved, which can make the patient have better function after the operation. This kind of operation leads to the increase of operation time and operation risk.